Exposure to bacterial and fungal bioaerosols in facilities processing biodegradable waste - Kontro, Merja H.; Kirsi, Maija; Laitinen, Sirpa K. (Frontiers in Public Health, 2022)
The aim of the study was to determine the bacterial and fungal risks to workers’ health in the processes of biodegradable waste. Occupational measurements were performed in seven composting and three bioenergy (bioethanol or methane) producing facilities. Bioaerosol samples were measured from workers’ breathing zones, and from their nasal mucous membranes. Bacteria and fungi from the air were collected to filters using Button Aerosol Samplers. Microorganisms (Aspergillus fumigatus, Campylobacter spp., Salmonella spp., Streptomyces spp., and Yersinia spp.) were determined by real-time polymerase chain reaction (qPCR) analysis. Actinobacteria and fungi were cultivated from filters. Bacterial airborne endotoxins collected by IOM samplers were analyzed using a Limulus assay. Bioaerosol levels were high especially in the composting compared to bioenergy producing facilities. Endotoxin concentrations often exceeded there the occupational exposure value of 90 EU/m3, which may be harmful to the health. In addition to endotoxins, the concentrations of A. fumigatus and Streptomyces spp. in the air were high, and these airborne microorganisms correlated with the same microbiological findings from nasal samples of workers. Campylobacter ureolyticus DNA was also general in the nasal mucous membranes of those workers, while as Campylobacter lanienae DNA was detected once in the air sample. The qPCR analysis of microbes made it possible to determine exposure to pathogens in various work environments, and samples from the nasal mucous membranes of workers showed their actual inhalation of microorganisms. That method helps to establish potential respiratory health risks and efficiencies of preventive measures and personal protection of workers.